Vivencias socioemocionales en familias de jóvenes con Síndrome de Down en Padre Las Casas, Chile - Antisoli Remolcoy, Yessica; Campusano Toledo, Claudia Daniela; Moraga Leiva, Teresa Maricel; Uberuaga Henríquez, María José; San Martín Cantero, Daniel; Tapia Gutiérrez, Carmen Paz (Universidad de Costa Rica, 2019)
This article aims to show the socio-emotional experiences of families with sons and daughters who have Down Syndrome. This is an investigation carried out during the year 2018, in which social relationships and emotional stages that restructure the life course of families are addressed. The methodological approach is qualitative, with a case study design. The participants were members of families of young people with Down Syndrome, members of a group for families of children with Down Syndrome in the commune of Padre Las Casas in Chile. The techniques for gathering information were semblances and biographical-narrative interviews. Inductive-deductive analysis is performed, and data triangulation is applied. The results were organized around five thematic axes: (i) receiving the news, (ii) socio-family support, (iii) experiences with schools, (iv) resilience, and (v) emotional course. It is concluded that socio-emotional experiences determine the life course of families. The interpreted significance showed to be useful to understand the role of health, educational and social institutions, and their contribution in learning processes, development and accompaniment of the boy, girl and their family.